9q31.2-rs865686 as a susceptibility locus for estrogen receptor-positive breast cancer: evidence from the Breast Cancer Association Consortium - Warren, Helen; Burwinkel, Barbara; Marmé, Frederik; Schneeweiss, Andreas; Sohn, Christof (Cancer epidemiology, biomarkers & prevention, 2012)
Background: Our recent genome-wide association study identified a novel breast cancer susceptibility locus at 9q31.2 (rs865686). - Methods: To further investigate the rs865686-breast cancer association, we conducted a replication study within the Breast Cancer Association Consortium, which comprises 37 case-control studies (48,394 cases, 50,836 controls). - Results: This replication study provides additional strong evidence of an inverse association between rs865686 and breast cancer risk [study-adjusted per G-allele OR, 0.90; 95% confidence interval (CI), 0.88; 0.91, P = 2.01 × 10−29] among women of European ancestry. There were ethnic differences in the estimated minor (G)-allele frequency among controls [0.09, 0.30, and 0.38 among, respectively, Asians, Eastern Europeans, and other Europeans; P for heterogeneity (Phet) = 1.3 × 10−143], but no evidence of ethnic differences in per allele OR (Phet = 0.43). rs865686 was associated with estrogen receptor-positive (ER+) disease (per G-allele OR, 0.89; 95% CI, 0.86-0.91; P = 3.13 × 10−22) but less strongly, if at all, with ER-negative (ER−) disease (OR, 0.98; 95% CI, 0.94-1.02; P = 0.26; Phet = 1.16 × 10−6), with no evidence of independent heterogeneity by progesterone receptor or HER2 status. The strength of the breast cancer association decreased with increasing age at diagnosis, with case-only analysis showing a trend in the number of copies of the G allele with increasing age at diagnosis (P for linear trend = 0.0095), but only among women with ER+ tumors. - Conclusions: This study is the first to show that rs865686 is a susceptibility marker for ER+ breast cancer. - Impact: The findings further support the view that genetic susceptibility varies according to tumor subtype. Cancer Epidemiol Biomarkers Prev; 21(10); 1783-. ©2012 AACR.